2023
DOI: 10.1088/1361-6463/ace36e
|View full text |Cite
|
Sign up to set email alerts
|

Release of Arabidopsis seed dormancy by cold atmospheric plasma relies on cytoplasmic glass transition

Abstract: When mature Arabidopsis thaliana seeds are dormant, their germination is prevented in apparently favourable conditions. This primary dormancy can be released during seed dry storage through a process called after-ripening whose duration can last several months. To reduce this delay, cold atmospheric plasmas (CAP) can be used as sources of reactive oxygen species capable of inducing heterogeneous chemical reactions. While CAP are known to stimulate the germination of various seed species, the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…In a prior study dedicated to Arabidopsis seeds, we have established that increasing WC make the seeds enter into an amorphous state, thereby reducing their cytoplasmic viscosity [10]. This so-called 'rubbery state' make the seeds more receptive to the effects of C2AP, especially to release their dormancy.…”
Section: Arabidopsis Seed Dormancy Is Released By Plasma Especially I...mentioning
confidence: 99%
See 2 more Smart Citations
“…In a prior study dedicated to Arabidopsis seeds, we have established that increasing WC make the seeds enter into an amorphous state, thereby reducing their cytoplasmic viscosity [10]. This so-called 'rubbery state' make the seeds more receptive to the effects of C2AP, especially to release their dormancy.…”
Section: Arabidopsis Seed Dormancy Is Released By Plasma Especially I...mentioning
confidence: 99%
“…Thus, in the medical field, cold plasma at lower dose can induce cell stimulation/proliferation for wound healing while at higher dose it can drive to senescence and cell death for oncology applications [7]. In agriculture and more specifically in the seed sector, cold plasmas are processed to improve germination parameters (vigor, homogeneity, dormancy release, tolerance to water stress) as well as optimal development of seedlings at early stages [8][9][10]. Cold plasmas are also designed to protect seeds from potential fungi (e.g.…”
Section: Influence Of Plasma On Seedsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is attributed to the modulation of the amorphous state of the seed cytoplasm. The amorphous properties of seed tissues and the water content within the seeds play a crucial role in regulating cytoplasmic viscosity, which in turn affects oxygen diffusion and the generation of reactive oxygen species (ROS), ultimately leading to dormancy release . In addition, research conducted by Waskow et al demonstrated that plasma treatment can induce significant changes in A.…”
Section: Introductionmentioning
confidence: 99%
“…The amorphous properties of seed tissues and the water content within the seeds play a crucial role in regulating cytoplasmic viscosity, which in turn affects oxygen diffusion and the generation of reactive oxygen species (ROS), ultimately leading to dormancy release. 21 In addition, research conducted by Waskow et al demonstrated that plasma treatment can induce significant changes in A. thaliana seeds. These changes include seed coat erosion, increased surface roughness, altered chemical composition (e.g., oxidation of carbon), and enhanced hydrophilicity.…”
Section: Introductionmentioning
confidence: 99%